Cardiac syncope recurrence in type 2 diabetes mellitus patients vs. normoglycemics patients: The CARVAS study. (May 2019) - Sardu, Celestino; Paolisso, Pasquale; Santamaria, Matteo; Sacra, Cosimo; Pieretti, Gorizio; Rizzo, Maria Rosaria; Barbieri, Michelangela; Scisciola, Lucia; Nicoletti, Gianfranco; Paolisso, Giuseppe; Marfella, Raffaele
Abstract: Study hypothesis: Cardiac autonomic dysfunction might lead to higher vaso vagal syncope (VVS) recurrence rate in type 2 diabetes mellitus (T2DM) patients vs. non diabetics patients. Background: VVS recurrence might be due to alterations of autonomic system function, as assessed by heart rate variability (HRV). To date, in this study we investigated the correlation between HRV alterations and VVS recurrence at 12 months of follow up in T2DM vs. non T2DM patients. Materials and methods: In a prospective multicenter study we studied a propensity score matching (PSM) analysis of 121 T2DM vs. 121 non T2DM patients affected by VVS. Results: T2DM vs. non T2DM patients had at baseline a higher rate of HRV dysfunction, and this was linked to higher rate of VVS recurrence at 12 months of follow up (p < 0.05). Blood pressure alterations and lower LF/HF ratio were linked to higher rate of all cause syncope recurrence, and of vasodepressor, cardio inhibitory, and mixed syncope recurrence (p < 0.05). Anti hypertensive drug therapies increased the number of vasodepressor and mixed syncope events (p < 0.05); alterations of heart rate increased syncope recurrence and mixed syncope recurrence events (p < 0.05). Finally, T2DM was linked to higher rate of VVS recurrence, and specifically of vasodepressor and mixed VVS recurrence (p < 0.05). Conclusions: T2DM patients have alterations of the autonomic nervous system, as result of cardiac autonomic neuropathy. However, T2DM diagnosis and autonomic dysfunction assessed by HRV alterations predicted VVS recurrence.